Empowerment pregnant women in preparation for lactation during the covid 19 pandemic - Siregar, Farida Linda Sari Siregar; Darti, Nur Afi; Br. Karo, Evi Indriani; Nurbaiti (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Empowerment of third trimester pregnant women in preparation for lactation during the COVID 19 pandemic is expected to help mothers achieve success in breastfeeding their babies after giving birth. The problem found during the pandemic was that there were restrictions on almost all routine services including maternal and neonatal health services so that pregnant women were reluctant to go to puskesmas or other health service facilities for fear of being infected and there were recommendations to postpone antenatal care and pregnancy classes. The aim of this community service is to empower pregnant women in the third trimester to prepare for lactation during the COVID-19 pandemic, to provide information support to pregnant women so that mothers are confident and confident about breastfeeding, creating a strong intention for mothers to breastfeed their babies exclusively. The service method used is health education, discussions, demonstrations and video screenings. The results of community service activities obtained by most of the knowledge of pregnant women, both about prevention efforts that pregnant women can take during the COVID 19 pandemic, how to care for breasts, how to position breastfeeding and the benefits of breastfeeding.